2005
DOI: 10.1111/j.1540-5907.2006.00175.x
|View full text |Cite
|
Sign up to set email alerts
|

Earthquakes and Aftershocks: Race, Direct Democracy, and Partisan Change

Abstract: Although dramatic partisan change among the electorate is infrequent, the issue agendas of parties may produce large shifts. A major cause of such change is the politics of race. In a political environment charged with racially oriented issues, racial groups often align themselves with different parties (as witnessed most recently in the American South). Yet, if racial appeals violate norms of equality, these appeals may rebound on the party using them. Consequently, members of the (white) racial majority and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
99
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(100 citation statements)
references
References 34 publications
1
99
0
Order By: Relevance
“…Therefore their partisan ties might be more cemented so that by adulthood the local political environment has much less of an influence. For newer generations, partisan attachments may not be as firmly cemented because their socialization to partisan politics is different (Alvarez and Bedolla 2003;Bowler, Nicholson, and Segura 2006). Furthermore, local partisan environments could have a greater influence on immigrants given that "community-level political activities are open to unauthorized immigrants and legal immigrants not yet eligible for naturalization (DeSipio 2011(DeSipio , 1193."…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore their partisan ties might be more cemented so that by adulthood the local political environment has much less of an influence. For newer generations, partisan attachments may not be as firmly cemented because their socialization to partisan politics is different (Alvarez and Bedolla 2003;Bowler, Nicholson, and Segura 2006). Furthermore, local partisan environments could have a greater influence on immigrants given that "community-level political activities are open to unauthorized immigrants and legal immigrants not yet eligible for naturalization (DeSipio 2011(DeSipio , 1193."…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Prior studies have shown how a single political environment that changes over time can influence Latino partisanship (Bowler, Nicholson, and Segura 2006). Yet few studies have examined how differences in political environments across regions might influence Latino partisanship.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, between 1980 and 1994, the GOP was beginning to drag Latinos to the right as well. Field Poll data make it clear that Latinos in the state were less Democratic every year between 1980 and 1994 (Bowler et al 2006). Ronald Reagan did well among Latinos in 1984 and the Immigration Reform and Control Act of 1986 was passed by a GOP Senate and signed by a GOP president.…”
Section: The First Momentmentioning
confidence: 99%
“…Although ballot initiatives with strong racial and ethnic dimensions have garnered a great deal of attention from scholars and political observers in recent years (Bowler, Nicholson, and Segura 2006;Nicholson 2005, chp.6;Tolbert and Hero 1996;Tolbert and Grummel 2003), perhaps no initiative figures more prominently in California political consciousness than Prop. 13.…”
mentioning
confidence: 99%